Characterization of polymer behavior in microchannels - Costa, M. (2013)
Microinjection moulding can be used to process monitoring and rheological characterization, can help to understand the behavior of polymer melt flows during the filing of micro cavities. The system used allows a study on characterization of polymer behavior in microchannels. This approach is appropriate since rheological phenomena such as wall slip, surface tension, melt pressure drop and polymer flow length can be studied. In this system, the data acquisition has made by incorporation of two sensors inside the mould.